O Dano moral e o dano extrapatrimonial nas relações trabalhistas - Bastos, Ana Paula Fleuri de (2020)
The analysis of the problematic of this work has as its starting point the appreciation of the legislation, the jurisprudence, the Brazilian doctrine and the norms of International Law, in order to answer the main question: The labor reform restricted, directly or indirectly, the repercussions compensation for off-balance sheet damages in relation to workers in contrast to the matrix of the Constitution of the Republic and the Brazilian Civil Code? The objective is, therefore, to study and analyze Law 13.467 / 2017, specifically in Title II-A, which brought off-balance-sheet damage as an innovation, with latent incompatibility with the established precepts and principles listed in the 1988 Constitution, in the Code International Standards. Thus, the research is based on theoretical statements of a general nature about personality rights and specifically demonstrates the impacts that the insertion of Title II–A of Law 13.467 / 2017, which regulates off-balance-sheet damages, brought to the labor law scene.